Prognostic value of coronary computed tomography angiography compared to radionuclide myocardial perfusion imaging in patients With coronary stents - Abazid, Rami M.; Romsa, Jonathan G.; Warrington, James C.; Akincioglu, Cigdem; Smettei, Osama A.; Bureau, Yves; Tzemos, Nikolaos; Vezina, William C. (Frontiers in Cardiovascular Medicine, 2023)
Background: The aim of this study is to compare the prognostic value of coronary computed tomography angiography (CCTA) with single-photon emission computed tomography (SPECT) in predicting cardiovascular events in patients with stents. Methods: Between January 2007 and December 2018, all patients post-percutaneous coronary intervention (PCI) who were referred for hybrid imaging with CTA and 2-day rest/stress SPECT were enrolled in this study. Patients were followed for any major adverse cardiovascular event (MACE) including: All-cause mortality, Non-fatal myocardial infarction (MI), Unplanned revascularization, Cerebrovascular accident and hospitalization for arrhythmia or heart failure. We define hard cardiac events (HCE) as: cardiac death, non-fatal MI or unplanned revascularization. We used two cut-off values to define obstructive lesions with CCTA ≥50% and ≥70% in any coronary segment. SPECT scan defined as abnormal in the presence of > 5% reversible myocardial perfusion defect. Results: In total, 119 patients were included in the final analysis. The mean age at enrolment was 62±9 years. The follow-up period was 7.2 ± 3.4 years. 45/119 (37.8%) patients experienced 57 MACE: Ten deaths (2 cardiac deaths and 8 of non-cardiac deaths), 29 acute coronary syndrome including non-fatal MI (25 required revascularization), 7 hospitalizations for heart failure, 6 cerebrovascular accidents and 5 new atrial fibrillation. 31 HCEs were reported. Cox regression analysis showed that obstructive coronary stenosis (≥ 50% and ≥ 70%) and abnormal SPECT were predictors of MACE (p = 0.037, 0.018 and 0.026), respectively. In contrast, HCEs were significantly predicted with obstructive coronary stenosis of ≥ 50% and ≥ 70% with p = 0.004 and p = 0.007, respectively. In contrast, abnormal SPECT was a nonsignificant predictor of HCEs (p = 0.062). Conclusion: Obstructive coronary artery stenosis on CCTA can predict MACE and HCE. However, abnormal SPECT can only predict MACE but not HCE in patients post-PCI with a follow-up period of approximately 7 years.